INTEGRATING E-PORTFOLIOS IN FLIPPED ENGLISH CLASSES: IMPACTS ON NURSING ESP SPEAKING - Bridgita Berlian Budiani; Sri Wuli Fitriati; Widhiyanto Widhiyanto; Sri Wahyuni (Linguists : Journal of Linguistics and Language Teaching, 2026)
This study examines the effectiveness of integrating e-portfolios into a flipped English classroom to enhance English for Specific Purposes (ESP) speaking performance and speaking self-efficacy among nursing students. Grounded in ESP pedagogy, communicative language teaching, and self-efficacy theory, the study addresses the persistent gap between students’ linguistic knowledge and their ability to perform professional oral communication in healthcare contexts. A quasi-experimental one-group pre-test-post-test design was implemented with 40 second-year nursing students at a private health sciences college in Central Java. The instructional intervention combined pre-class input, in-class communicative practice, and iterative speaking development through e-portfolio-based recording, feedback, and reflection over one academic semester. Speaking performance was assessed through task-based ESP speaking tests, while self-efficacy was measured using a Likert-scale questionnaire. The findings revealed statistically significant improvements in both speaking performance and speaking self-efficacy, with large effect sizes indicating substantial educational impact. The results suggest that integrating e-portfolios within a flipped classroom expands opportunities for structured practice, fosters reflective learning, and strengthens learners’ confidence, thereby supporting both linguistic and psychological dimensions of professional communication. The study underscores the pedagogical value of technology-supported, contextually grounded speaking instruction in health sciences education and recommends the combined use of flipped learning and e-portfolio-based formative assessment to promote sustainable ESP speaking development.